Complex Decongestive Therapy in the Physical Therapist Management of Rosacea-Related Edema (Morbus Morbihan Syndrome): A Case Report With a New Approach. Issue 9 (17th May 2021) - Çinar, Gamze Nalan; Özgül, Serap; Nakip, Gülbala; Üzelpasaci, Esra; Baran, Emine; Gürşen, Ceren; Elçin, Gonca; Akbayrak, Türkan
Abstract: Objective: The aim of this case report was to describe the use of complete decongestive therapy (CDT) with a new approach in the management of a male with facial edema related to Morbus Morbihan Syndrome (MMS). Methods: An 18-year-old male with MMS after acne treatment was the subject of this case report. Volume assessment was performed with distance measurements of the facial area using standard reference points, the overflow method, and the measurement of the percentage of subdermal fluid. Participant-reported symptoms of lymphedema (feeling of swelling and tightness) and body image perception were evaluated with the visual analogue scale, and the severity of anxiety was evaluated with the State and Trait Anxiety Inventory. In addition, the participant's perception of improvement was determined using a Likert-type scale. Evaluations were performed at baseline, week 4 (during the treatment), and week 8 (immediately after treatment). CDT was applied to the participant in a total of 24 sessions, 3 d/wk for 8 weeks. Results: Compared with the baseline measurement, the facial distances (tragus-mental cavity, tragus-mouth corner, mandibula-nasal canal, mandibula-internal orbita, mandibula-external orbita, mental cavity-internal orbita, mental cavity-mandibula, right–left tragus, and hairline in the forehead-mental cavity), the volume, and the percentage of subdermal fluid of facial area were decreased at the week 4 and 8 measurements. The anxiety score, participant reports of feelings of swelling and tightness, and body image perception improved after the 8 weeks of treatment compared with baseline. Conclusion: This case report described the use of CDT in treating edema and participant symptoms in an individual with facial lymphedema related to MMS. Body image and level of anxiety improved.